2003
DOI: 10.1029/2002gl016500
|View full text |Cite
|
Sign up to set email alerts
|

Current sheet flapping motion and structure observed by Cluster

Abstract: Fast vertical flapping oscillations of the plasma sheet have been observed by Cluster on September 26, 2001. The flapping motion had vertical speeds exceeding 100 km/s, an amplitude in excess of 1 RE and a quasiperiod of ∼3 min. The current sheet was mostly tilted in the Y‐Z plane (with the tilt sometimes exceeding 45°). The waves had the properties of a kink mode and propagated toward the dusk flank. The flapping allowed to probe the vertical structure of the plasma sheet. Three different methods gave consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

51
305
3
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(360 citation statements)
references
References 13 publications
51
305
3
1
Order By: Relevance
“…Karimbadi et al (2003) showed by full particle and hybrid simulations that the velocity shear, resulting from the presence of secondary ion population, drives the ion-ion kink (IIK) mode instability, which produces B x variations similar to the observed, and a displacement of the current peak from the sheet center to lobes. The calculated wavelength (2.8 R E ) and period (90 s) are close to the values which were found by Runov et al (2003) and Sergeev et al (2003).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Karimbadi et al (2003) showed by full particle and hybrid simulations that the velocity shear, resulting from the presence of secondary ion population, drives the ion-ion kink (IIK) mode instability, which produces B x variations similar to the observed, and a displacement of the current peak from the sheet center to lobes. The calculated wavelength (2.8 R E ) and period (90 s) are close to the values which were found by Runov et al (2003) and Sergeev et al (2003).…”
Section: Discussionsupporting
confidence: 69%
“…Similar behaviour of the plasma density was observed by Sergeev et al (2003) within the bifurcated current sheet (26 September 2001 event). In both cases the average plasma density in the central part of the current sheet is ∼0.2 cm −3 , which is slightly lower than the average density of 0.3−0.4 cm −3 found by Baumjohann et al (1989) from a statistical analysis of AMPTE/IRM spacecraft data within geocentric distances 10<R<19 R E .…”
Section: Ion Properties Within the Bifurcated Current Sheetsupporting
confidence: 60%
See 1 more Smart Citation
“…It has been observed in Cluster case studies that a wave moving in the dawn-dusk direction could cause a neutral sheet very steeply inclined toward the Y-axis (Zhang et al, 2002;Sergeev et al, 2003). Further statistical studies revealed that this dawn-dusk wave is kink-like and has a preCorrespondence to: T. L. Zhang (tielong.zhang@oeaw.ac.at) ferred propagation direction from the tail center to flank (Sergeev et al, 2004;Runov et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Kivelson (1991) and Bauer et al (1995a, b) and references therein. Also, the whole magnetotail can be flapping (Sergeev et al, 1998(Sergeev et al, , 2003. The experimental investigations have not been limited to the Earth's magnetotail, but have also been extended to the magnetotails of the outer planets (Khurana et al, 1992).…”
Section: Introductionmentioning
confidence: 99%